AI Integration in RISE with SAP : Enhancing Operational Efficiency and Decision- Making in Manufacturing through Cloud Migration to SAP S/4HANA - Luong, Huu Loc; Hönig, Vladimír, 1982-; Procházka, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This master’s thesis examines how integrating AI within the RISE with SAP framework affects operational efficiency and decision-making in manufacturing companies. The study uses a mixed-methods approach, combining quantitative multiple regression analysis of survey data with qualitative thematic analysis of open-ended responses. The quantitative analysis outcomes validate that the use of AI for analytics and automation boosts how well manufacturing works and improves decision-making quality. Meanwhile, the thematic analysis depicts crucial user concerns about the need for AI capabilities tailored to manufacturing, transparency, customization, and alignment with strategic goals. The findings show the potential and challenges of using AI in manufacturing, providing practical recommendations for SAP and industry professionals. Even though there are some limitations with the sample size and the way the study was designed, this thesis offers essential insights on improving AI tools to enhance innovation and competitiveness in manufacturing companies.
Vedoucí práce: Vladimír Hönig
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses